Comparison of human metapneumovirus, respiratory syncytial virus and Rhinovirus respiratory tract infections in young children admitted to hospital. Issue 2 (30th July 2014) - Adams, O.; Weis, J.; Jasinska, K.; Vogel, M.; Tenenbaum, T.
<x xml:space="preserve">Abstract</x> Respiratory Syncytial Virus (RSV), Human metapneumovirus (HMPV), and Rhinoviruses (RV) are frequent causes of respiratory tract infections in young children. We compared laboratory and clinical findings in children with comparable age distribution and hospitalized due to RSV, HMPV or RV infections. Viral pathogens were detected by a quantitative real time PCR from nasopharyngeal aspirates. No significant differences in the admission diagnosis, laboratory parameters, patient demographics and treatment measures between the three viral causes of respiratory illness were found. No correlation between viral load and disease severity was observed however, there was a significantly lower concentration of the nasopharyngeal interleukin 8 (IL‐8) in children with RV compared to HMPV and RSV, indicating a milder proinflammatory reaction. Moreover, RV‐infected children had significantly lower body temperature, higher leucocyte counts in peripheral blood, and a tendency to have a shorter stay in hospital than children with either HMPV or RSV infection. Taken together, clinical presentation of the infections with RSV, HMPV, and RV is similar among children of the same age group and not clearly distinguishable by standard clinical or laboratory findings. Therefore, virus specific testing should be included regularly for routine diagnosis of children with respiratory tract infections. J. Med. Virol. 87:275–280, 2015. © 2014 Wiley Periodicals, Inc.